The Influence of Al-Quran Reading Fluency and Self-Confidence on the Reading Mastery of Islamic Boarding School - Muslichuddin Muslichuddin; Fattah Khoirun; Aminudin Aminudin; Nur Hasanah (Nurul Jadid University, 2025)
This study aims to analyze the influence of Quranic reading fluency and self-confidence on students' mastery of Quranic reading at Ma'had Al-Hidayah, Batu City. The background of this study stems from the importance of Quranic reading skills as a foundation for students in understanding classical religious texts (yellow books), as well as the role of self-confidence as a psychological factor that fosters courage and active participation in the learning process. This study used a quantitative approach with multiple linear regression. The sample consisted of 40 students selected through purposive sampling. Data were obtained through questionnaires and Quranic reading ability tests, then analyzed using SPSS. The results showed that simultaneously, Quranic reading fluency and self-confidence had a positive and significant effect on students' mastery of Quranic reading, contributing 49.7%. Partially, Quranic reading fluency exerted a more dominant influence than self-confidence. These findings indicate that linguistic skills derived from familiarizing themselves with reading the Quran serve as the primary foundation for understanding the yellow text, while self-confidence strengthens students' mental readiness and courage in the learning process. This research emphasizes the importance of implementing integrative learning strategies that balance cognitive and affective aspects in Islamic boarding school education to optimally improve students' Quran literacy skills.